Investigations on dual laser beam welding of aluminum high pressure die castings at reduced ambient pressure - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (Journal of Laser Applications, 2018)
During the manufacture of aluminum high pressure die castings, the aluminum alloy is in a liquid phase during the majority of process steps. Due to the high solubility of hydrogen in liquid aluminum, the die casted part likely has an increased hydrogen content, which affects the weldability negatively. When welding these materials, hydrides dissociate and hydrogen is liberated and forms porosity during solidification. To avoid the described formation of porosity, friction stir welding below the melting point and electron beam welding with high frequency beam oscillation were investigated in prior research. Other studies reported that the formation of porosity during laser beam welding of pure aluminum was prevented by the application of dual beam configurations. However, it is well known that laser beam welding under vacuum condition has several advantages, such as the increase in penetration depth, the enhanced degasification, or the overall calming effect on the melt pool when welding ferrous metals. Aiming to combine these advantages, the current work consequently focuses on the occurrence of porosity during dual laser beam welding of aluminum die castings under vacuum (100–0.1 hPa) and atmospheric conditions. All results are based on the outcome of x-ray computed tomography or tensile testing.
Keywords: aluminium alloys; aluminium alloys; computerised tomography; die casting; laser beam welding; oscillations; tensile testing; computerised tomography; die casting; laser beam welding; oscillations; tensile testing